Two New Species and One New Genus of Glass Sponges (Hexactinellida: Euplectellidae and Euretidae), From a Transect on a Seamount in the Northwestern Pacific Ocean - Shen, Chengcheng; Cheng, Hong; Zhang, Dongsheng; Wang, Chunsheng (Frontiers in Marine Science, 2022)
Hexactinellid sponges often form structural habitats for other organisms and thus support high biodiversity. Two representative morphotypes of hexactinellid sponges were sampled by a remotely operated vehicle along a transect (depths of 2377–2758 m) on the Ko-Hakucho Guyot in the northwestern Pacific Ocean, both new to science. One new species, Flavovirens hemiglobus gen. et sp. nov., which is pedunculate and bears the main choanosomal spicules of diactins, is clearly attributed to the euplectellid subfamily Bolosominae. Its set of microscleres present (namely, predominating oxyhexasters and discasters, and rare discohexasters and staurodiscs) characterizes it as a new genus. The other new species, Chonelasma tyloscopulatum sp. nov., which is funnel in form without dichotomous branching tubes or lateral oscula and has firm body walls supported by a three-layered dictyonal framework, is clearly attributed to the euretid genus Chonelasma (subfamily Chonelasmatinae). Its presence of surface pentactins, two types of scopules, and both oxy- and disco-tipped hexasters or hemihexasters as common microscleres, characterizes it as a new species. The placements are also supported by molecular phylogenetic evidence from nuclear 18S rDNA and 28S rDNA, and mitochondrial 16S rDNA and cytochrome c oxidase subunit I (COI) gene. More sampling efforts should be conducted to improve the understanding of the biodiversity of deep-sea seamount sponges.